Cartographic Approach in Studying Landscape Morphology and Dynamics in Northwestern Part of Western Siberia - Kuzmenko, Ekaterina (Recent Progress in Plant and Soil Research Vol. 1, 2021)
The structure and dynamics of geosystems: plant of forest and bogs in the northwestern part of Western Siberia is considered by using the Kazym-Lyamin interfluve, based on the landscape-as-assessment map for the middle part of the Khanty-Mansi Autonomous District. The study used the landscape structural-dynamical approach and the methods of studying the spatio-temporal dynamics of taiga geosystems. Theoretical and methodological research on the development of the landscape-assessment map for Asian Russia is high on the cartographic agenda of the V. B. Sochava Institute of geography SB RAS. The methodic research is to be used to Landsat-5 TM and the Hansen mosaic in GIS MultiS-pec and Qgis. An analysis is also made of the topographic, geomorphologic and forest 1:200,000 maps, the profiles characterize the lithology, field data of geobotanical and soil de- scriptions, and experimental permanent station operated. Presented are the technique and results of studying the landscape structure of the north-west of Western Siberia on the basis of the Hansen mosaic dataset consisting of elements covering the entire territory of the Earth. The landscape structure of this area and its hierarchic-al subordination are represented in the map legend in terms of groups of facies which are combined into regional-typological classification units: groups of geoms, classes, and types of natural environment. Landscape mapping and planning will help to timely prevent and forecast the magnitudes of disturbances to natural environment using and be as the basis for a package of optimal nature-conservation measures and target-oriented technogenic and anthropogenic impacts.